Quality monitoring of soybean seed tests using Statistical Process Control - Alcantara, Aline S. [UNESP]; Prado, Jessica P. do [UNESP]; Correa, Rafael de G. [UNESP]; Silva, Rouverson P. da [UNESP]; Voltarelli, Murilo A.; Vieira, Roberval D. [UNESP] (Univ Federal Campina Grande, 2018)
The success of soybean cultivation depends on several factors, one which is the use of high-quality seeds, which can guarantee growth of the desired plant population. The objective of this study was to monitor possible failures during the seed production process, and to determine the association between germination and tetrazolium tests through tools of Statistical Process Control (CEP). The experimental design was based on premises of the CEP, using percentage of germination, seed viability, mechanical damage, bed bug, and moisture as indicators of quality. It is possible to detect flaws in the soybean production process through control charts, as well as through germination and tetrazolium tests; results indicated that germination failures are largely caused by mechanical damage and bed bug attacks.
Keywords: Glycine max L.; control charts; quality indicators; seed viability